Analysis of Calculation, Deposit and Reporting Value Added Tax and Income Tax in Construction Service Companies: Case study on CV. ABC Kendari - Jumaria, Sumarni Lilu; Hajar, Ibnu; Nur, Muhammad (Journal of Business Management and Economic Development, 2024)
This study aims to determine and analyze the application of Calculation, Deposit and Reporting of Value Added Tax and Income Tax at Construction Services Company CV. ABC Kendari Period Year 2022. This research uses a qualitative descriptive method. Data collection techniques through interviews and literature studies regarding tax data and financial reports of CV. ABC Kendari during the 2022 period. The results of this study indicate that the application of the calculation, deposit and reporting of Value Added Tax and Final Income Tax Article 4 Paragraph (2) that has been carried out by CV. ABC Kendari as a company that has been confirmed as a Taxable Entrepreneur is in accordance with the General Provisions and Procedures for Taxation and the current Legislation and every work completed is made a Tax Invoice in accordance with the value stated in the Pay Order or Disbursement Order received from the Government Agency or Office Treasurer as a service user.